Technology and gender violence. A study in two schools in Costa Rica - Fernández Fernández, Daniel (2025)
Introduction: This article reflects how the rise of information and communication technologies have come to occupy a central role in social relationships amongst adolescents, as well as in the continuation of gender violence from online spaces to offline spaces in the context of romantic relationships. Objective: Study the manifestation of gender violence in adolescent romantic relationships and their relation with the use of information and communication technologies in two public schools in Costa Rica during 2022. Methodology: A descriptive quantitative strategy has been developed, which uses frequency analysis of the main variables under study. Results: The results coincide with other research in this area which indicates that social networks constitute one of the principal means of socialization amongst adolescents. On the other hand, the data shows that digital media is of great importance when it comes to establishing romantic relationships. Finally, the responses provided by the people surveyed make it possible to identify various situations of violence that occur, whether in romantic relationships between adolescents or in romantic relationships between an adolescent and an adult. Conclusions: These results, even if they cannot be generalized to all adolescents, coincide with the prevalence rates of gender violence across virtual media as shown by different research carried out in other contexts.